Tocqueville and Beaumont Aristocratic Liberalism in Democratic Times - Hess, Andreas (Springer International Publishing, 2018)
This is the first concise study to give full credit to the collaboration of works between French nobleman, writer and politician Alexis de Tocqueville (1805-59) and his travel companion and friend Gustave de Beaumont (1802-66), and puts this collaboration into its social, historical and theoretical context. It accompanies the two friends to the US and analyses the fruitful encounter between the New and the Old World that was the result of that journey, particularly in relation to emerging Atlantic democracies and revolutions. This includes the hopes but also the problems and contradictions that they have come to represent. The book also follows Tocqueville and Beaumont to England, Ireland, and Algeria. It discusses their political careers and their engagement in the abolitionist movement, their fight for liberal social and political reform, as well as their futile attempt to rationalize French colonization in Algeria.